ESTIMATOR TWO STAGE LEAST SQUARES (2SLS) PADA MODEL PERSAMAAN STRUKTURAL DENGAN VARIABEL LATEN - , MIFTAHULKHAIRAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Structural Equation Model (SEM) with latent variable is a powerful tool for social and behavioral scientists, because it combines a lot of psychometrics and econometrics into a single framework. The estimator often used in SEM is Maximum Likelihood Estimator (MLE). When the high properties desired, the MLE and the other full information estimators will otherwise remain lacked. The main thing is that when a part of the model misspecified, almost always the case. The bias can be spread on the specific model, because the model parameter estimation is conducted simultaneously. With these reasons, the optional alternative study is continuous limited information estimator